KAJIAN SIFAT FISIKA TANAH PADA AREAL TANAMAN KARET (Hevea brasiliensis) YANG SUDAH TIDAK PRODUKTIF DI PTP NUSANTARA III RAMBUTAN (The Study of Soil Physical Properties in Unproductive Rubber Plantations (Hevea brasiliensis) of PTP Nusantara III Ramb - Hasanul Basri Siregar; Sumono Sumono; Delima Lailan Sari Nasution (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT Soil physical properties is an important factor for plant growth. The research was aimed to examine the soil physical properties of unproductive rubber plantations (Hevea brasiliensis) at PTP. Nusantara III Rambutan. The research used survey and soil analysis methods and conducted at The Research and Technology Laboratory of the Faculty of Agriculture, University of North Sumatra and Research Center Laboratory of palm oil research centre in Medan. The parameters observed were soil texture, organic matter, porosity, depth of soil effectiveness, soil permeability and water availabilety. The results showed that the type of the soil on Afd.5 PTP. Nusantara III Rambutan was Inceptisol, with textured sandy loam, the content of organic materials at a depth of 5 cm was ranged from 0,84 % - 1,67 % and at a depth  of 25 cm was ranged from 0,40 % - 0,93 %, porosity of soil at a depth of 5 cm was ranged from 46,33 % - 48,00 % and at a depth  of 25 cm was ranged from 46,00 % - 46,66 % with effective depth of soil in ferns, grass and taros were 54 cm, 58 cm and 57 cm, respectively soil permeability at a depth of 5 cm was ranged from 6.17 cm/hr – 17.85 cm/hr and at a depth 25 cm was range from 0.35 cm/hr – 0.83 cm/hr, the amount of water available for vegetated fields of grasses, grasses and taros were 7,00%, 5.96% and 9.21%. Respectively poor soil physical properties in the area Afd. 5 PTP Nusantara III Rambutan was categorized. Keywords: Inceptisol, Soil Physics, Rubber, Unproductive. ABSTRAK   Sifat fisika tanah merupakan faktor penting bagi pertumbuhan tanaman. Penelitian ini bertujuan untuk mengkaji sifat fisika tanah pada areal tanaman karet   (Hevea brasiliensis)  yang sudah tidak produktif di kebun PTP. Nusantara III Rambutan. Penelitian menggunakan metode survei dan analisa tanah dilakukan di Laboratorium Riset dan Teknologi Fakultas Pertanian Universitas Sumatera Utara dan Laboratorium Pusat Penelitian Kelapa Sawit Medan. Parameter yang diamati meliputi tekstur tanah, bahan organik,  porositas,  kedalaman efektif tanah, permeabilitas tanah dan air tersedia.  Hasil penelitian menunjukkan jenis tanah pada lahan Afd. 5 PTP. Nusantara III Rambutan adalah Inceptisol, bertekstur lempung berpasir, kandungan bahan organik pada kedalaman 5 cm berkisar antara 0,84 % - 1,67 % dan pada kedalaman 25 cm berkisar antara 0,40 % - 0,93 %. Porositas tanah pada kedalaman 5 cm berkisar antara 46,33 % - 48,00 % dan pada kedalaman 25 cm berkisar antara 46,00 % - 46,66 %, kedalaman efektif tanah pada pakis, rumput dan keladi yaitu 54 cm, 58 cm dan 57 cm,  permeabilitas tanah pada kedalaman 5 cm berkisar antara 6,17 cm/jam - 17,85 cm/jam dan pada kedalaman 25 berkisar antara 0,35 cm/jam – 0,83 cm/jam, Jumlah air tersedia untuk lahan bervegetasi pakis, rumput dan keladi yaitu  7,00 %;  5,96 % dan 9,21 %. Sifat fisika tanah pada areal Afd. 5 PTP Nusantara III Rambutan dikategorikan kurang baik.   Kata Kunci: Fisika Tanah, Inceptisol, Karet, Tidak Produktif.